2008
DOI: 10.4321/s1130-01082008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la endotelina-1 sobre las arterias tumorales de pacientes con neoplasia colorrectal

Abstract: INTRODUCCIÓNLos vasos sanguíneos que irrigan los tumores presentan alteraciones tanto morfológicas (1) como funcionales (2,3) y estas características de los vasos tumorales pueden ser relevantes para favorecer el crecimiento y expansión del tumor, modificando el flujo sanguíneo al mismo. Uno de los factores que pueden estar implicados en la regulación del flujo sanguíneo en condiciones normales y patológicas es la endotelina-1, un péptido producido por las células endoteliales y que presenta un potente efecto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Moreover, prior reports showed that ET-1 is an important mediator of myogenic tone in isolated tumor arterioles and that tumor-feeding arterioles may be particularly sensitive to ET-1. 28,29 Thus, it was conceivable that elevated levels of ET-1 secreted locally by ET-1 cancer cells might lead to constriction of the adjacent vasculature to perturb blood flow to the tumor site. In support of this we made the following findings: (1) Treatment of mice with the vasodilator hydralazine led to a significant increase in the growth of ET-1 tumors, although it did not completely restore it to the level in the vector control; (2) Hydralazine treatment increased perfusion of ET-1 tumors; and (3) Vascular casts from ET-1 tumors showed constriction of afferent arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior reports showed that ET-1 is an important mediator of myogenic tone in isolated tumor arterioles and that tumor-feeding arterioles may be particularly sensitive to ET-1. 28,29 Thus, it was conceivable that elevated levels of ET-1 secreted locally by ET-1 cancer cells might lead to constriction of the adjacent vasculature to perturb blood flow to the tumor site. In support of this we made the following findings: (1) Treatment of mice with the vasodilator hydralazine led to a significant increase in the growth of ET-1 tumors, although it did not completely restore it to the level in the vector control; (2) Hydralazine treatment increased perfusion of ET-1 tumors; and (3) Vascular casts from ET-1 tumors showed constriction of afferent arterioles.…”
Section: Discussionmentioning
confidence: 99%